The Influence of Tacit knowledge on Competitive Advantage: Learning from ICT Service Providers in Nairobi - Mucai, John Muigai (Archives of Business Research, 2018)
The strategic management scholarly landscape is replete with conceptual literature on resource- and knowledge-based theories that single out tacit knowledge as an important driver of competitive advantage. This is not matched by empirical studies that have explicitly tested these ideas. This study contributes towards filling this gap. The study followed positivist and post-positivist critical realism philosophical orientations, using a cross-sectional survey design approach. The population for the study was the ICT content service providers licensed by the Communications Authority of Kenya (CAK). Out of the target population of 197 ICT content service providers, 135 firms provided valid responses to the survey. The study affirmed the importance of tacit knowledge as a resource that contributes to the competitiveness of a firm relative to its peers. This is an additional building block in strategic management theories that show the importance of continuous enhancement of the productive knowledge of individuals in an organization in increasing the competiveness of the organization.